2017
DOI: 10.1017/s0025100317000366
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic transfer in language contact: Evidence for equivalence classification in the mid-vowels of Occitan–French bilinguals

Abstract: This article examines first to second language (L1-to-L2) phonetic transfer in the speech of ten Occitan–French bilinguals, focusing on the mid-vowels in each of their languages. Investigating transfer in a situation of long-term societal language contact aims to shed light on the emergence of regional French phonological features from contact with Occitan. Using a sociophonetic methodology, the concept of equivalence classification (Flege 1988) is investigated, that is, that L2 words will be (initially) decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It is also a kind of development. Such development is normally observed when learners realize some difference between an L2 sound and the closest L1 sound, but they cannot acquire such an L2 sound accurately (Mooney, 2019;Syed & Saleem, 2019).…”
Section: Presentation Of Datamentioning
confidence: 99%
“…It is also a kind of development. Such development is normally observed when learners realize some difference between an L2 sound and the closest L1 sound, but they cannot acquire such an L2 sound accurately (Mooney, 2019;Syed & Saleem, 2019).…”
Section: Presentation Of Datamentioning
confidence: 99%
“…The current study contributes to a growing body of variationist work examining transfer in situations of long-term bilingualism (e.g., Davidson 2015;Nagy 2015;Mooney 2019;Gafter and Horesh 2020). One particular strand of this research has been the analysis of speech in contexts of language revitalisation, wherein a clear distinction in speech patterns has been found between so-called 'new speakers', who have acquired the language outside of the home, and 'traditional speakers' (e.g., Nance 2013Nance , 2015.…”
Section: Introductionmentioning
confidence: 90%
“…Although evidence for bilingual dominance, and thus exposure, effects for children's phonetic patterning is fairly scarce (but see Bijeljac-Babic, Serres, Höhle, and Nazzi 2012), these influences are well-documented for adults in situations of language contact (Henriksen, García-Amaya, Coetzee, and Wissing 2019, Mooney 2019, Onosson and Stewart 2021, Simonet 2011, Yao and Chang 2016. For example, Guion (2003) found that age of Spanish acquisition affected the ability of Quichua-Spanish speakers in highland Ecuador to partition the vowel space across the two languages.…”
Section: Exposure Effects In Bilingual Developmentmentioning
confidence: 99%